Weed interference on organic carrot yield under different sowing methods - Souza, Luís Gustavo de Souza e; Félix Ferreira, Regina Lúcia; Elviro de Araújo Neto, Sebastião; Lemos Uchôa, Thays; Mendes da Silva, Nilciléia; Penha Pinto, Geazí; de Moura Francisco, Wagner; Bezerra da Silva, Sandra (Comunicata Scientiae, 2025)
Weed cause serious problems to vegetable cultivation, justifying the importance of studies on the interference of these plants in agricultural crops and management techniques in the context of organic production. From this perspective, this study aimed to evaluate the interference of weed on the yield of carrot grown under different sowing methods. The study was conducted at the Seridó Ecological Station in Rio Branco, Acre, Brazil. Control and coexistence experiments with weeds were set up in a split-plot design (5 x 2), with the plot corresponding to the coexistence or control periods: 15, 20, 25, 30, and 35 days after sowing, and the subplots corresponding to the sowing methods: direct seeding and water conditioning. Cultivation followed the recommendations for carrot and for the organic system. The harvest and evaluations were performed after 80 days by evaluating the biometric variables, the carrot yield, and the weed mass. The statistical analysis consisted of the test of assumptions followed by analysis of variance. Non-linear regression was used for the yield parameters by determining the interference periods. In contrast, linear regression was used for the other variables. Carrot coexistence with weeds reduced the conventional commercial yield by 75.73% and the organic commercial yield by 57.07%. Organic carrot cultivation should occur free of weed from 21 to 28 days. Water conditioning increased the organic carrot yield.